2021
DOI: 10.3389/fimmu.2021.744430
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Cyclophosphamide-Induced Transplantation Tolerance in Mice and Its Relationship With the HLA-Haploidentical Bone Marrow Transplantation/Post-Transplantation Cyclophosphamide Platform

Abstract: The bone marrow transplantation (BMT) between haplo-identical combinations (haploBMT) could cause unacceptable bone marrow graft rejection and graft-versus-host disease (GVHD). To cross such barriers, Johns Hopkins platform consisting of haploBMT followed by post-transplantation (PT) cyclophosphamide (Cy) has been used. Although the central mechanism of the Johns Hopkins regimen is Cy-induced tolerance with bone marrow cells (BMC) followed by Cy on days 3 and 4, the mechanisms of Cy-induced tolerance may not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
(215 reference statements)
0
2
0
Order By: Relevance
“…Cyclophosphamide (Endoxan) was chosen as the immunosuppressor. Studies have reported that the post-transplantation administration of cyclophosphamide induces transplantation tolerance in mice and is also considered a form of graft-versus-host disease prevention [66][67][68][69]. Allogeneic nonmyeloablative bone marrow transplantation with post-transplantation cyclophosphamide administration has also been applied in the treatment of nonmalignant hematological disorders [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…Cyclophosphamide (Endoxan) was chosen as the immunosuppressor. Studies have reported that the post-transplantation administration of cyclophosphamide induces transplantation tolerance in mice and is also considered a form of graft-versus-host disease prevention [66][67][68][69]. Allogeneic nonmyeloablative bone marrow transplantation with post-transplantation cyclophosphamide administration has also been applied in the treatment of nonmalignant hematological disorders [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…The existing approaches to serotherapy or immunomagnetic depletion of T cells are largely non-selective if the aim of the process is to restrict the alloreactive T-cell population alone. In a series of preclinical studies, groups from Japan and Johns Hopkins U n i v e r s i t y i n t h e U S A h a v e s h o w n t h a t hi g h -d o s e cyclophosphamide (Cy), if administered 2-3 days after graft infusion, can result in long-term tolerance in mismatched mice models (26,27). Cy and its active metabolite are rapidly metabolized by aldehyde dehydrogenase (ALDH) and cells that lack ALDH are far more susceptible to Cy-induced death.…”
Section: Post-transplantation Cyclophosphamide-simple Yet Elegantmentioning
confidence: 99%